2015
DOI: 10.1016/j.trsl.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary salt levels on monocytic cells and immune responses in healthy human subjects: a longitudinal study

Abstract: Increasing evidence indicated that excess salt consumption can impose risks on human health and a reduction in daily salt intake from the current average of approximately 12 g/d to 5–6 g/d was suggested by public health authorities. The studies on mice have revealed that sodium chloride plays a role in the modulation of the immune system and a high-salt diet can promote tissue inflammation and autoimmune disease. However, translational evidence of dietary salt on human immunity is scarce. We used an experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
129
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 44 publications
4
129
1
3
Order By: Relevance
“…Of note, recent studies in patients with autoimmune diseases indicated that higher salt intake is associated with increased clinical and radiological disease activity in MS patients and with increased risk of developing rheumatoid arthritis (28,29). Moreover, a recent longitudinal study under highly controlled conditions in humans indicated that changes in dietary salt levels could significantly impact cellularity of cells of the innate immune system and secreted levels of pro-and antiinflammatory cytokines such as IL-6, IL-23, and IL-10 in vivo (30). Besides raising interstitial sodium content, high-salt diets potentially exert direct effects on lymphocytes in gut-associated tissues and within the intestine (25).…”
Section: Secretion Of Ifnγ By Foxp3mentioning
confidence: 99%
“…Of note, recent studies in patients with autoimmune diseases indicated that higher salt intake is associated with increased clinical and radiological disease activity in MS patients and with increased risk of developing rheumatoid arthritis (28,29). Moreover, a recent longitudinal study under highly controlled conditions in humans indicated that changes in dietary salt levels could significantly impact cellularity of cells of the innate immune system and secreted levels of pro-and antiinflammatory cytokines such as IL-6, IL-23, and IL-10 in vivo (30). Besides raising interstitial sodium content, high-salt diets potentially exert direct effects on lymphocytes in gut-associated tissues and within the intestine (25).…”
Section: Secretion Of Ifnγ By Foxp3mentioning
confidence: 99%
“…These findings were also accompanied by a higher exacerbation rate in patients with medium and high sodium intake compared with the normal‐intake group 76. Interestingly, there is a positive correlation between the amount of salt consumed and IL‐17 plasma levels in healthy individuals 83. However, a recent large European–Canadian trial study in MS patients treated with interferon‐β1b did not find any association between salt intake and MS activity or progression in this cohort 84.…”
Section: Salt and Msmentioning
confidence: 70%
“…demonstrated in a long‐term longitudinal study that there is a strong positive correlation between serum monocytes and dietary salt intake in healthy donors. Interestingly, high salt intake was associated with increased levels of IL‐6 and IL‐23 and decreased levels of IL‐10, thus creating a milieu that promotes T H 17 differentiation 83. Furthermore, 1 week of high salt diet in healthy volunteers resulted in expansion of nonclassical CD14 + CD16 + monocytes and monocyte–platelet aggregates with enhanced reactive oxygen species production by monocytes 89…”
Section: Salt and Msmentioning
confidence: 99%
“…Yi et al [26] found a higher number of monocytes in the blood of healthy individuals with high dietary salt intake (12 g/d) than the individuals with normal dietary salt intake. It is of interest that reducing salt intake led to increased production IL-10 and decreased production of IL-23 and IL-6 by lymphocytes [26].…”
Section: Salt-derived Inflammationmentioning
confidence: 99%
“…It is of interest that reducing salt intake led to increased production IL-10 and decreased production of IL-23 and IL-6 by lymphocytes [26].…”
Section: Salt-derived Inflammationmentioning
confidence: 99%